HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN KEPATUHAN PENGGUNAAN ALAT PELINDUNG DIRI PEKERJA BAGIAN PENGOLAHAN ASPAL DI JALAN RAYA KECAMATAN MEDAN SUNGGAL - Nadhrah Himayah Gea; Tri Niswati Utami (Universitas Pahlawan, 2022)
ABSTRACT The obedience of the worker in obeying the use of apd is determined by two factors which are individual and work factors, obedience to the use of apd is determined by knowledge in the worker, as the working day will affect the quantity and quality of the worker to the job. Worker knowledge will change behavior so that a change of attitude will create a worker's attitude to conform to the rules of the job. The aim of this research is to analyze the relationships of knowledge and worker behavior with adherence to the self-protection of workers who plant asphalt in the pangal terrain highway. The study used a kind of quantitative study with analytic methods using a sectional cross-sectional research approach with a number of 52 respondents. Variables studied are knowledge and the worker's attitude toward use compliance. Personal protective equipment. Data analysis USES the chi square test, data collection USES a questionnaire. Based on chi square's test came ata value of sign-p 0.001 smaller than 0.5, it was concluded that there was a connection between the knowledge and the attitude of the personal use of protective protective equipment part of the bitumen treatment road across the waterfront. Companies are encouraged to enhance training and supervising programs for workers to enhance the knowledge and attitude of the workers Keywords: PPE, compliance, knowledge, worker, attitude